2015
DOI: 10.4172/2161-0932.1000319
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Abdominal Cysts: Prenatal Diagnosis and Management

Abstract: Objective: Fetal intra-abdominal cystic masses are quite rare entities and their differential diagnosis is particularly perplexing. These masses encompass many different pathological cysts originating from almost every organ in the abdomen. In female fetuses, ovarian cysts are the primary cause. In our study, we investigated the techniques used in diagnosis, accuracy of methods and management strategies, and tried to summarize postnatal outcomes. Materials and methods:A total of 29 cases were evaluated retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…However, accurate identification is challenging, even during childhood, due to the resemblance and diversity of the focal abdominal cystic lesions ( 9 , 10 ). Accumulating evidence indicates that the pre- and postnatal outcomes of fetal abdominal cysts may be associated with organ origin, gestational age at diagnosis, ultrasound characteristics and size at diagnosis ( 7 , 11 13 ). A recent multi-institutional retrospective cohort study reported that clear organ of origin, diagnosis earlier in gestation, initial prenatal cyst diameter and sonographic cyst characteristic changes can contribute to the differentiation and management of congenital ovarian cysts ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, accurate identification is challenging, even during childhood, due to the resemblance and diversity of the focal abdominal cystic lesions ( 9 , 10 ). Accumulating evidence indicates that the pre- and postnatal outcomes of fetal abdominal cysts may be associated with organ origin, gestational age at diagnosis, ultrasound characteristics and size at diagnosis ( 7 , 11 13 ). A recent multi-institutional retrospective cohort study reported that clear organ of origin, diagnosis earlier in gestation, initial prenatal cyst diameter and sonographic cyst characteristic changes can contribute to the differentiation and management of congenital ovarian cysts ( 14 ).…”
Section: Introductionmentioning
confidence: 99%